2019
DOI: 10.1038/s41418-019-0411-9
|View full text |Cite
|
Sign up to set email alerts
|

Translating neural stem cells to neurons in the mammalian brain

Abstract: The mammalian neocortex underlies our perception of sensory information, performance of motor activities, and higherorder cognition. During mammalian embryogenesis, radial glial precursor cells sequentially give rise to diverse populations of excitatory cortical neurons, followed by astrocytes and oligodendrocytes. A subpopulation of these embryonic neural precursors persists into adulthood as neural stem cells, which give rise to inhibitory interneurons and glia. Although the intrinsic mechanisms instructing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 161 publications
(216 reference statements)
4
54
0
Order By: Relevance
“…For example, cortical progenitors express Brn1 and Tle4 mRNAs, for both deep and superficial layer fates, respectively, but their translation into the corresponding proteins is initially repressed by a translational repression complex and subsequently released in due time (Zahr et al, 2018). Micro-RNAs are especially interesting in this respect and they have been indicated as heterochronic modulators of vertebrate development (Gulman et al, 2019;Robinton et al, 2019), also in the context of the vertebrate nervous system (Chiu et al, 2014;Nowakowski et al, 2018;Zahr et al, 2019). camo et al, 2008;Britanova et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cortical progenitors express Brn1 and Tle4 mRNAs, for both deep and superficial layer fates, respectively, but their translation into the corresponding proteins is initially repressed by a translational repression complex and subsequently released in due time (Zahr et al, 2018). Micro-RNAs are especially interesting in this respect and they have been indicated as heterochronic modulators of vertebrate development (Gulman et al, 2019;Robinton et al, 2019), also in the context of the vertebrate nervous system (Chiu et al, 2014;Nowakowski et al, 2018;Zahr et al, 2019). camo et al, 2008;Britanova et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that eukaryotic initiation factor 4E1 (eIF4E1) and the eIF4E-Binding Protein, 4E-T, components of the eukaryotic translational machinery, form P-body-like complexes that bind proneural bHLH mRNAs to inhibit their translation, a mechanism of translational control critical for controlling the timing of cortical neurogenesis ( Yang et al, 2014 ) ( Figure 3A ). Since then, many additional proteins have been identified that control the translation of proneural and neural differentiation genes, including other components of the translational machinery and critical RNA binding proteins ( Amadei et al, 2015 ; Zahr et al, 2018 , 2019 ). Future work will be required to identify specific RNA binding proteins that control the stability and translation of proneural gene transcripts.…”
Section: Regulation Of Proneural Gene Function At the Translational Amentioning
confidence: 99%
“…The radial glia will generate neurons during the later stages of neurogenesis as well as astrocytes and oligodendrocytes further during gliogenesis and oligodendrocytogenesis, respectively. 56 In the adult mammalian brain NSCs are found in the ventricular-subventricular zone and the subgranular zone. In addition to NFs, neurons may also express other intermediate filaments such as nestin and vimentin.…”
Section: Different Ifs Conjoin In the Cnsmentioning
confidence: 99%
“…Neurogenesis is initiated early during development when neural stem cells from the neural tube give rise to progenitor cells called radial glia. The radial glia will generate neurons during the later stages of neurogenesis as well as astrocytes and oligodendrocytes further during gliogenesis and oligodendrocytogenesis, respectively 56 . In the adult mammalian brain NSCs are found in the ventricular‐subventricular zone and the subgranular zone.…”
Section: Neuronal Cell Fatementioning
confidence: 99%